THE USE OF PROJECT-BASED LEARNING TO IMPROVE STUDENTS` SPEAKING SKILLS IN EFL CLASSROOM AT SMPS TANRA TELLUE - Hamzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to investigate the effectiveness of Project-Based Learning (PjBL) in improving the speaking skills of eighth-grade students at a rural junior high school in South Sulawesi, Indonesia, specifically in terms of accuracy (pronunciation, vocabulary, grammar) and fluency (smoothness and self-confidence). A pre-experimental one-group pretest-posttest design was employed, involving 34 students selected through purposive sampling. The intervention consisted of four structured PjBL sessions over four weeks, incorporating collaborative projects such as dialogue creation, role-plays, and video presentations. Data were collected through speaking performance tests assessed using an analytic rubric and complemented by classroom observations. Quantitative data were analyzed using descriptive statistics, a paired-sample t-test, and Cohen`s d effect size. The findings revealed a statistically significant improvement in students` overall speaking performance, with the mean score increasing from 68.2 (Fair) in the pretest to 82.4 (Good) in the posttest (t(33) = -8.742, p < .001). The effect size was very large (d = 1.87). Observational data confirmed increased student engagement from 67% to 81%. The study concludes that PjBL effectively creates an authentic, collaborative, and low-anxiety learning environment that enhances both the accuracy and fluency of speaking skills among rural junior high school students.